(untitled) (One Health & Risk Management, 2023)
Introduction. The habit of drinking water in sufficient quantities appears when people understand its importance for their organism. Water is vital for survival and there is currently great interest in the benefits of good hydration for people to function, look and feel good. Water makes up a large proportion of our body weight (60% on average), distributed between the intracellular and extracellular compartments. It is also the major component of body fluids, such as blood, synovial fluid, saliva and urine, which perform vital functions in the body. The concentration of solutes in body fluids is closely controlled, and even very small changes in osmolality trigger a physiological response, either to increase body water by reducing urinary output and stimulating thirst, or to excrete excess water as urine. Dehydration can be defined as a loss of 1% or more of body mass. The balance of water in the body is determined by how much fluid is consumed plus the small amount of water produced by metabolism in the body versus the amount of water lost from the body. Water loss occurs via the kidneys as urine, through the skin as sweat, in feces, evaporation from the lungs and skin. Aim. The purpose of this study was to determine if medical students, who know about the importance of water, use sufficient amounts daily. Material and methods. The study was carried out on a group of 100 students, second year from the Nicolae Testemitanu State University of Medicine and Pharmacy. The study instrument included a questionnaire with 12 questions regarding water consumption for physiological needs. A questionnaire was used and the students answered through the Google forms application. The study group consisted of 40 girls (40%) and 60 boys (60%). Results. Being medical students, all of them know the benefits of drinking enough water, but the largest percentage (45%) of student’s daily drink water less than 0,5 liters, which is a small amount for the human body needs to establish physical activity and physiological processes. 85% of respondents consider that they need to drink more water, but don’t have this good habit. All the students answered that they use bottled water for drinking, because compared to tap water it is safer from the point of view of chemical composition and microbiological safety. Most respondents (67%) replace water with other liquids, such as tea, coffee, juice, cola and other types of liquids, although everyone knows that it is wrong and nothing can replace water in the human body for physical activity and physiological processes. In relation to the time of day, 42% drink water in the morning, and 24% before bedtime, 58% don’t drink in the morning, 76% don’t drink before going to sleep. Conclusions. Promoting a healthy lifestyle among students, who will be future doctors is very important for their health and for recommendations to their future patients. Water is essential to life and maintaining optimal hydration is important for the body to function efficiently. The requirements for the amount of water to be consumed depend largely on age, sex, body mass, environmental conditions and everyone’s physical activity.